Autocicatrização de concretos com uso de aditivo cristalizante - Tambara, Rafael Fumaco (2024)
This study investigated the influence of the incorporation of a crystalline admixture (CA) on self-healing in structural concretes made with Portland cement (CP-V ARI-RS) and subjected to pre-loading by axial compression at different ages (7 and 28 days). For each loading age, three samples of each mix were tested for compressive strength, and the average rupture value was used to determine the percentage of load that would be applied to the concrete (0%, 50%, and 80% of the average fck). To stimulate self-healing, the samples were submerged in water from when they were produced until their respective test ages. The samples were only removed from curing during the pre-loading stage. Samples preloaded at 7 days were tested at 14, 28, 56, and 91 days, while samples preloaded at 28 days were tested at 35, 56, and 91 days. The control tests selected were axial compressive strength, water absorption by capillarity (Kelham method), and ultrasonic wave propagation velocity. In addition, some samples were analyzed using optical microscopy images to monitor the formation of self-healing products over time. The results obtained allow us to conclude that (i) the axial compressive strength test showed that concrete with CA and without loading had the best mechanical performance of the mixtures investigated; (ii) the evaluation of ultrasonic wave propagation velocity with time variation showed an increase in ultrasonic velocity in concretes incorporating CA and preloaded at 7 and 28 days, regardless of the percentage of loading applied (0%, 50% and 80%), indicating the repair of microcracks; (iii) concretes that were not preloaded showed similar patterns of reduction in average values of water absorption capillarity, regardless of the presence of the crystalline admixture. However, it is noteworthy that the concrete with added CA showed superior resistance to water absorption compared to the reference concrete, especially under pre-loading conditions; (iv) for optical microscopy image analysis, the reference concretes showed no significant surface healing, while the concretes with added CA showed partial filling of the cracks through the precipitation of calcium carbonate. In short, the tests carried out in this research corroborate the benefits of adding a crystalline admixture to concrete, especially its ability to self-heal.